Treatment of Patients with Multiple Sclerosis in Home Care — a Case Study - Barbara Jewczak (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Background. Multiple sclerosis (Multiplex Sclerosis — MS) is a disease of the nervous system. It often poses difficulties in diagnosing which makes detection of the disease in the early stages of its development difficult without specialized tests with the fact that more that people get sick at a young age. Studies also show that MS occurs (rarely) in children and in people over 60 years of age. The clinical course of multiple sclerosis is different, and the treatment is complicated due to theprogressive disease process. Consequently, there is a variety of patient problems in all areas of quality of life. Case study. The case study concerns a sixty-year-old man diagnosed with multiple sclerosis suffering from the disease since 2001, moving in a wheelchair, dependent on the help of others, subject to environmental home care. The paper presents selected individual problems and needs in a patient with proposed activities exercised by professionals (nurse, physiotherapist, guardian, psychologist, therapist, physician) and the immediate family. Discussion. The role of the caregiver who takes care of patients with multiple sclerosis at home is not easy. This personmust be practically round the clock to deal with the patient, which often leads to malaise and fatigue. Extending the time ofcare can lead to disorders occuring in the caregiver’s mental health (mainly associated with mood and fatigue) who often require professional help. Conclusions. Multiple sclerosis is an incurable disease, progressive and completely changing the patient’s life. In the case being studied, the patient’s problems are mainly in two areas — physical and mental. With the development of the disease, physical capacity is steadily deteriorating along with its deteriorating mental state of the patient. Several years of observations described the case of worse functioning of a patient during the autumn and winter. Important role in the management ofpatients plays rehabilitation and active exercise treatments, which the patient uses and keep him in relatively good physical condition. (PNN 2013; 2(5): 216–222)